2017
DOI: 10.19082/4215
|View full text |Cite
|
Sign up to set email alerts
|

Exploring perceptions of instructors about childbirth preparation training courses: A qualitative study

Abstract: BackgroundChildbirth preparation training courses on maternal and neonatal health increase awareness, and capability of pregnant women in overcoming fear and anxiety and managing labor pains.ObjectiveTo identify the affecting factors and barriers of these courses from the perspective of their instructors.MethodsThis qualitative study of the content analysis type, has been conducted on 16 certified teachers of the training courses of the Hamadan city in 2015. Data were collected by semi-structured in-depth inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The ndings showed that the situations of facilities of maternity hospitals do not adapt the content of the classes, the timing of the start of the classes are not appropriate, and they are not announced correctly. Previous studies have assessed the factors in uencing childbirth preparation classes; e.g., a study conducted by Otogara (2017) reported the need for presence of a psychologist consultant, as well as appropriate timing and information for successful implementation of classes [59].…”
Section: Discussionmentioning
confidence: 99%
“…The ndings showed that the situations of facilities of maternity hospitals do not adapt the content of the classes, the timing of the start of the classes are not appropriate, and they are not announced correctly. Previous studies have assessed the factors in uencing childbirth preparation classes; e.g., a study conducted by Otogara (2017) reported the need for presence of a psychologist consultant, as well as appropriate timing and information for successful implementation of classes [59].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, nulliparaous women were determined to experience fears such as unknown fear, inability to cope with contractions and loss of control during delivery because they were inexperienced and uneducated. Also, it was found that childbirth preparation education increased the awareness of women by their false beliefs about the childbirth process (Otogara et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The women said the education had very much reduced their fears, and that it had taught them to manage the processes related to pregnancy, childbirth and postpartum. Similarly, antenatal education maternity preparation education (Otogara et al, 2017) raised women's awareness in coping with fears. Women gained the ability to manage all of the processes and learn the methods of pain relief and pain management skills in relation to their own roles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 5-40% of pregnant women fear childbirth in western countries, and a recent study reported that Chinese pregnant women have moderate levels of childbirth fear and anxiety [5]. It is estimated that out of every five pregnant women, one has a fear of natural childbirth, and, in most women, fear of birth leads to increased anxiety, pain and prolonged labour [6]. Depression and anxiety are common mental disorders during pregnancy and after childbirth worldwide [7].…”
Section: Introductionmentioning
confidence: 99%